2014
DOI: 10.1159/000358229
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia Makes Cerebral Resistance Index a Poor Prognostic Tool in Encephalopathic Newborns

Abstract: Background: Severe neonatal encephalopathy (NE) of hypoxic-ischaemic origin may cause death or life-long disability. Acute encephalopathy may also affect cerebrovascular control. Pourcelot's cerebrovascular resistance index (RI) ≤0.55 was predictive of poor outcome in normothermic NE infants. Recent studies have questioned its predictive power during therapeutic hypothermia (HT). Objective: To assess the predictive power of RI during HT and after rewarming. Methods: 45 infants with NE treated with HT for 72 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 46 publications
0
25
0
1
Order By: Relevance
“…If an RI is performed early enough after admission and before or simultaneous with the onset of TH, a low RI value may retain some of its prognostic value [30]. Its predictive value returns once the infant is rewarmed [31]. The reason for a loss of the predictive value of a low RI during TH is not well understood.…”
Section: Doppler Ultrasonography and Resistive Indicesmentioning
confidence: 99%
“…If an RI is performed early enough after admission and before or simultaneous with the onset of TH, a low RI value may retain some of its prognostic value [30]. Its predictive value returns once the infant is rewarmed [31]. The reason for a loss of the predictive value of a low RI during TH is not well understood.…”
Section: Doppler Ultrasonography and Resistive Indicesmentioning
confidence: 99%
“…There are a number of clinical circumstances where an assessment of regional perfusion could add to our understanding of pathophysiological changes in blood flow that put infants at risk of neurological injury [6,7]. Assessing changes in perfusion over time, such as during the transitional period after birth, or in circumstances when abnormal perfusion might be expected, such as after an ischaemic insult, requires a reference range for comparison.…”
Section: Introductionmentioning
confidence: 99%
“…The second hypothesis is that the hypothermia itself has a larger effect on perfusion of the thalamus than the anterior cerebral artery, and the change in the RI difference on day 4 was due to a return to normothermia at that time. Previous studies demonstrated decreased positive predictive values of the anterior cerebral artery RI for predicting death or severe disability when infants are undergoing hypothermia versus measurements obtained during normothermia . Because all 3 neonates in the hypothermia group developed our primary outcome of death or CP, we were unable to differentiate between these hypotheses in this study.…”
Section: Discussionmentioning
confidence: 79%